PENGEMBANGAN MEDIA KOMIK DIGITAL PADA PEMBELAJARAN PELESTARIAN LINGKUNGAN KELAS V TEMA VIII DI SEKOLAH DASAR - Nadila Rahmi; M. Jaya Adi Putra; Jesi Alexander Alim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the product of digital comics that can ease teachers to convey material and enable students to understand the subject matter. Type of the research is Research and Development (R&D) with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The research subjects involved researchers as media designers, media experts, material experts, linguists, teachers, and students. The instrument of data collection uses a questionnaire. The questionnaire used is a validation sheet and a product trial questionnaire. The results of the PE conducted by validators and practitioners on digital comic media, which consists of six assessment aspects obtained an average score of 86.40% with a very valid category. Validation validated by media experts achieved 78%. Validation validated by material experts achieved 89%. Validation validated by linguists achieved 84%. validation validated by practitioner I achieved 93% and validation from practitioner II achieved 94%. Thus, the results of the average score obtained 87.6% with a very valid category. The results of the one-on-one trial with three students obtained 82.5%with a very decent category. In addition, the results obtained from a limited trial of 13 students obtained an average score of 88.65% with a very decent category.